THE EFFECTIVENESS OF VALIDATION MEASUREMENTS IN AUTOMATED SYSTEMS OF THE POWER SUPPLY SYSTEMS CONTROL IN ACCORDANCE WITH LIMIT VALUES - V. A. Anishchenko; T. V. Pisaruk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
A high level of operational reliability of power supply systems is virtually impossible to provide without operational control of the reliability of the measurement variables (currents, voltages, powers, energies, temperatures, pressures) that characterize the condition of power equipment and technological processes. Reforming the power engineering and its transition to market relations necessitate one to toughen the requirements for the reliability of the measuring information. Inaccurate measurements are a potential source of misdiagnosis of malfunctions of equipment and they cause incorrect operation of emergency control equipment and erroneous actions of operating personnel in the control of technological processes. Operational methods of reliability control that enhance the operational reliability of the measuring information are based on the usage of the semantic value of the measured data, their consistency, process consistency, and consistency of balance. These methods use technological sense of the measured variables and they complement the methods of hardware status monitoring of automated control systems based on digital codes. That improves the overall operational reliability of the transmission, collection and processing of information. The most common semantic method of control is the method of limits (“fork”) that compares the numeric value of the measured variable with the upper and lower boundaries of valid values. The disadvantage of limit values in many cases is its poor resolution, due to the wide range of appearance of results of measurements. This reduces the probability of detection of gross and systematic errors of measurements more than it may be accepted. With this regard, the objective of a reasonable narrowing of the range of valid values of the variables, that uses the theory of statistical decisions, acquires high relevance.